2008
DOI: 10.1021/bi702385k
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Carbonic Anhydrase II by Thioxolone: A Mechanistic and Structural Study

Abstract: This paper examines the functional mechanism of thioxolone, a compound recently identified as a weak inhibitor of human carbonic anhydrase II by Iyer et al. (2006) J. Biomol. Screening 11, 782-791. Thioxolone lacks sulfonamide, sulfamate, or hydroxamate functional groups that are typically found in therapeutic carbonic anhydrase (CA) inhibitors, such as acetazolamide. Analytical chemistry and biochemical methods were used to investigate the fate of thioxolone upon binding to CA II, including Michaelis-Menten k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 90 publications
1
44
0
Order By: Relevance
“…A similar CA II complex has been determined crystallographically and was recently published by Barrese et al[20] Investigating the inhibition profile and binding mode of thioxolone 6 in CA II, they observed that the inhibitor, most likely a prodrug, is hydrolyzed upon binding to form the fragment 4-thiobenzene-1,3-diol 7 ( K i =148 µm)[20] (Figure 4). However, superposition of 7 with 4 shows significant differences in the binding mode, with 7 binding in a monodentate fashion (Figure 3b, c).…”
Section: Discussionmentioning
confidence: 60%
“…A similar CA II complex has been determined crystallographically and was recently published by Barrese et al[20] Investigating the inhibition profile and binding mode of thioxolone 6 in CA II, they observed that the inhibitor, most likely a prodrug, is hydrolyzed upon binding to form the fragment 4-thiobenzene-1,3-diol 7 ( K i =148 µm)[20] (Figure 4). However, superposition of 7 with 4 shows significant differences in the binding mode, with 7 binding in a monodentate fashion (Figure 3b, c).…”
Section: Discussionmentioning
confidence: 60%
“…38 To determine whether the interactions perturbing 1,2-HOPTO binding apply to other MBPs containing similar donor sets, methyl derivatives of TP and 2MP analogous to 4-CH 3 -1,2-HOPTO were obtained and their binding to hCAII investigated. While 3-CH 3 -TP has similar inhibitory activity to unsubstituted TP ( K i = 2.1 μM vs 3.5 μM), the 4-methyl analogue of 2MP is significantly more potent (0.52 vs 3.1 μM).…”
Section: Resultsmentioning
confidence: 99%
“…100 The inhibition mechanism of this molecule was not immediately clear analyzing its chemical structure but crystallographic studies helped to clarify it. 100 In particular, in hCA II crystals soaked with 1, the latter was not found in the active site, which instead contained a 4-mercaptobenzene-1,3-diol molecule (2) bound to the catalytic zinc ion (Figure 9). This observation led to hypothesize that when thioxolone binds to the hCA II active site, it is cleaved forming 4-mercaptobenzene-1,3-diol via the intermediate S-(2,4-thiophenyl)hydrogen thiocarbonate (see Scheme 2) utilizing, as hypothesized for other esters, 101 a hCA II zinc-hydroxide mechanism.…”
Section: Thiol Derivativesmentioning
confidence: 99%